The Role of Midwives in the Education of Labor and Childbirth Readiness - Masita; Erlin Puspita; Yunita Laila Astuti; Nurmiaty (Universitas STRADA Indonesia, 2023)
Background: Efforts to reduce maternal mortality ratio can be done promotively, preventively, curatively, and rehabilitatively. One of the promotive efforts is to provide education during pregnancy, especially in the third trimester or before the estimated delivery. Childbirth preparation education is essential for pregnant women, husbands and families to improve knowledge and skills, one of which is the prevention and early detection of complications. The World Health Organization strongly recommends strengthening preparedness programs for childbirth and complications to increase utilization of quality care at delivery and to increase the use of health services for obstetric and newborn complications. Purpose: This study aims to identify the implementation of childbirth readiness education to prevent complications of childbirth in independent midwife practices in the DKI Jakarta area. Methods: Qualitative research design was used in this study with an explanatory descriptive design. Informants for this research were 15 midwives in the DKI Jakarta area. Selection of informants using purposive sampling technique. Analysis was done by means of data reduction, data presentation, and conclusion verification. Results: The implementation of labor and childbirth readiness education to prevent labor complications was quite good. Education on physical, psychological, and financial preparation has been carried out adequately, but there were several aspects of education related to cultural preparation related to pregnancy and childbirth that was still not optimal. Conclusion: It is expected that midwives can maintain the education that has been given to pregnant women. Midwives actively participate in monitoring and educating pregnant women so that they can carry out early detection of complications and appropriate treatment if emergencies occur.